Promoting Reading Culture in Samosir through Mobile Library Initiatives - Rahmat Alifin Valentino (EPISTEMOLOGI : JURNAL PENGABDIAN MASYARAKAT DAN PENELITIAN, 2025)
This study explores the role of mobile library initiatives in promoting a reading culture in remote and underserved areas. Limited access to educational resources, infrastructure, and books has long posed a challenge to literacy development in rural communities. In response, mobile libraries have emerged as a grassroots solution, bringing books and literacy programs directly to isolated populations. Using a qualitative descriptive approach, data were collected through interviews, focus group discussions, and observations in several remote villages served by mobile libraries. The findings indicate that mobile libraries significantly enhance access to reading materials, improve reading behavior among children and youth, and foster community engagement in literacy activities. Additionally, the study highlights the importance of local participation and identifies key challenges, such as sustainability, funding, and logistical constraints. Despite these obstacles, mobile library initiatives demonstrate a positive impact on educational equity and literacy development. The study concludes that with adequate support and strategic collaboration, mobile libraries have the potential to become sustainable instruments for empowering marginalized communities through reading.